2014
DOI: 10.1088/0963-0252/23/6/064011
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the upper-limit intensity in relativistic and ponderomotive self-focusing by using plasma with a linear electron temperature ramp

Abstract: This paper presents an investigation of the characteristics of the propagation of a Gaussian laser beam through an underdense plasma in the presence of a linear electron temperature ramp. Relativistic and ponderomotive nonlinearities are involved. It is shown that the ponderomotive nonlinearity induces a saturation mechanism in the self-focusing phenomenon and leads to the existence of a laser intensity threshold above which the beam starts to diverge. It is also found that on using the plasma electron tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…Moreover, this treatment introduces a turning point for laser intensity value (here 3 × 10 15 W/cm 2 ) where the self-compression is observed to the maximum extent. Both specific range and the turning point for laser intensity are observed, in similarity with previous analyses [25,37] performed for the self-focusing process. Physically, this behaviour may be linked with depletion of the electron density in the axial region, so that the larger or smaller gradient of dielectric permittivity (∇𝜀 ∝ 𝜀 𝜏 ), which is responsible for the pulse compression, is obtained.…”
Section: (B)supporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, this treatment introduces a turning point for laser intensity value (here 3 × 10 15 W/cm 2 ) where the self-compression is observed to the maximum extent. Both specific range and the turning point for laser intensity are observed, in similarity with previous analyses [25,37] performed for the self-focusing process. Physically, this behaviour may be linked with depletion of the electron density in the axial region, so that the larger or smaller gradient of dielectric permittivity (∇𝜀 ∝ 𝜀 𝜏 ), which is responsible for the pulse compression, is obtained.…”
Section: (B)supporting
confidence: 87%
“…[18,19] Numerous efforts have been done on the high-intensity laser beam evolution in the plasma. [20][21][22][23][24][25][26][27][28][29] The electromagnetic filamentation instability in the magnetized plasmas taking into account the relativistic electron mass variation and magnetic field perturbations has been studied by Shukla et al [20] Shibu et al have investigated the compression possibility of the laser pulse in a relativistic plasma and observed that the nonlinear self-focusing interferes with the self-compression mechanism. [15] Brandi et al [21] studied the propagation of high-intensity short laser beams in an inhomogeneous plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we think that the deformations in Figs. 5(ii) and 5(iii) may be caused by the modulational instability. Moreover, the fact that the increase of L with ω > 3.83 displayed in Figs.…”
Section: Propagation Dynamics and Stability Of Em Solitary Wave By Pi...mentioning
confidence: 99%
“…The nonlinear interaction between an intense electromagnetic (EM) pulse and plasmas is of great interest in various fundamental research and technological applications, including harmonic generation, [1][2][3] self-focusing, [4][5][6] wakefield generation, [7,8] relativistic optical guiding, [9][10][11] x-ray, [12] laser pulse frequency shifting, [13] pulse compression, [14] relativistic EM soliton propagation. [15][16][17][18][19] Among spectacular phenomena in nonlinear interactions, relativistic EM solitary waves have attracted a great deal of attention in a fundamental point of view, also due to their possible applications in inertial confinement fusion and the charged particle acceleration.…”
Section: Introductionmentioning
confidence: 99%